Integrating Project‐Based Learning With Self‐Regulated Learning to Enhance Programming Learning Motivation. - Gu, Peidi; Cheng, Zui; Miaoting, Cheng; Poggio, John; Dong, Yan (Journal of Computer Assisted Learning, 2025)
Background: Today, the importance of STEM (Science, Technology, Engineering and Mathematics) education and training is widely recognised and accepted. Computer programming courses have become essential in higher education to nurture students' programming, analysis and computational skills, which are vital for success in all STEM fields and areas. Objectives: This study evaluated an integrated pedagogical method that combined Project‐Based Learning (PBL) and Self‐Regulated Learning (SRL) to enhance college students' motivation when learning C programming. While PBL promotes learner‐centred environments, it does not automatically foster SRL, which is critical for sustaining engagement and motivation in cognitively demanding programming courses. Although research highlights the importance of both PBL and SRL, studies explicitly combining these frameworks to support motivation, emotion regulation, and learning satisfaction are limited. Our study addresses this gap by integrating SRL scaffolding into the PBL framework, hypothesising that this combination would positively impact students' learning motivation. Methods: The study used a pre‐ and post‐test quasi‐experimental design. A total of 173 students volunteered to participate. Students were randomly assigned to one of three pedagogical design groups: the PBL group, the PBL + SRL group or a control (traditional instruction) group. A one‐way analysis of covariance (ANCOVA) was the principal method for data analysis. Results and Conclusions: The study's findings demonstrated that the proposed PBL + SRL approach effectively enhanced students' intrinsic motivation. This is evidenced by the heightened interest and perceived value of the learning method and reduced tension and pressure throughout the learning process compared to both the standalone PBL and traditional approaches. Furthermore, students in the PBL + SRL group reported the highest self‐efficacy and course satisfaction levels. Contribution: This study pioneered the provision of empirical evidence supporting SRL scaffolding as an effective and timely intervention to improve students' learning motivation beyond using the PBL strategy alone in computer programming courses.